Assessing the Cost of Financial Regulation - Elliott, Douglas; Santos, Andre (Washington, D.C. : International Monetary Fund, 2012)
This study assesses the overall impact on credit of the financial regulatory reforms in Europe, Japan, and the United States. Long-term cost estimates are provided for Basel III capital and liquidity requirements, derivatives reforms, and higher taxes and fees. Overall, average lending rates in the base case would rise by 18 bps in Europe, 8 bps in Japan, and 28 bps in the United States. These results are similar to the official BIS assessments of Basel III and an OECD analysis, but lower as a result of including expense cuts and reductions in the returns required by investors. As a result, they are markedly lower than those of the IIF.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet